2004
DOI: 10.1128/mcb.24.15.6788-6798.2004
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 Regulates G1/S Progression by Suppressing Src Kinase Activity

Abstract: Cancer genes exert their greatest influence on the cell cycle by targeting regulators of a critical checkpoint in late G 1 . Once cells pass this checkpoint, they are fated to replicate DNA and divide. Cancer cells subvert controls at work at this restriction point and remain in cycle. Previously, we showed that RACK1 inhibits the oncogenic Src tyrosine kinase and NIH 3T3 cell growth. RACK1 inhibits cell growth, in part, by prolonging G 0 /G 1 . Here we show that RACK1 overexpression induces a partial G 1 arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 56 publications
3
79
1
1
Order By: Relevance
“…Consequently, the inhibition of SRC results in kinaseinactive SRC inducing a G1/S block and delayed G1/S transition. [45][46][47][48] However, SRC inhibitors induced dosedependent anemia, edema and erythema and affected the ovaries and liver in rats. 49 Limited enzymatic selectivity, which is not correlated to the compound's core structure and which led to inhibition of other kinases in non-targeted tissues, may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the inhibition of SRC results in kinaseinactive SRC inducing a G1/S block and delayed G1/S transition. [45][46][47][48] However, SRC inhibitors induced dosedependent anemia, edema and erythema and affected the ovaries and liver in rats. 49 Limited enzymatic selectivity, which is not correlated to the compound's core structure and which led to inhibition of other kinases in non-targeted tissues, may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…RACK1 was also recently implicated into a regulation of G 1 /S progression by binding to Src and suppressing its kinase activity, while use of siRNA for RACK1 activated Src-mediated signaling, induced myc and cyclin D1 and accelerated G1/S progression. 54 Numerous reports shown that MDM2 family members function as E3 ubiquitin ligases that mediate monoubiquitination of p53, its export from nucleus to cytoplasm and then targeting it into a proteasome machinery. [55][56][57] However, other proteins (e.g., COP1, PIRH2) were found to interact with p53 and might also perform this function.…”
Section: Discussionmentioning
confidence: 99%
“…Using a yeast two-hybrid assay, we identified RACK1 as a novel substrate and binding partner of Src and an endogenous inhibitor of Src kinase activity and cell growth (Chang et al, 1998(Chang et al, , 2001(Chang et al, , 2002. We showed that RACK1 exerts its effect on colonic cell growth, in part by suppressing Src activity at G 1 and mitotic checkpoints (Mamidipudi et al, 2004a(Mamidipudi et al, , 2007. We hypothesize that RACK1 regulates other aspects of cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we showed that RACK1 regulates colonic cell growth, in part by suppressing Src activity at G 1 and mitotic checkpoints (Mamidipudi et al, 2004a(Mamidipudi et al, , 2007. Another potential mechanism by which RACK1 could regulate growth is by inducing apoptosis.…”
Section: Rack1 Induces Apoptosis Of Human Colon Cells Partly By Inhimentioning
confidence: 99%